Effect of an inactivated coronavirus disease 2019 vaccine, CoronaVac, on blood coagulation and glucose: a randomized, controlled, open-label phase IV clinical trial - Xu, Qing; Lu, Xi; Liu, Xiaodong; Zhao, Yanwei; Sun, Dapeng; Cao, Qingfan; Liu, Haidong; Yang, Tuantuan; Song, Yufei; Lv, Jingjing; Xiong, Ping; Li, Jing; et al. (Frontiers in Immunology, 2023)
Background: Billions of doses of coronavirus disease 2019 (COVID-19) vaccines have been administered and several cases of thrombocytopenia with thrombosis syndrome (TTS) have been reported after the administration of adenoviral vector vaccines. However, the effects of an inactivated COVID-19 vaccine, CoronaVac, on coagulation are not well understood. Methods: In this randomized, controlled, open-label phase IV clinical trial, 270 participants including 135 adults aged 18–59 years and 135 adults aged 60 years or older, were enrolled and randomized to the CoronaVac group or to the control group in a 2:1 ratio and received two doses of CoronaVac or one dose of the 23-valent pneumococcal polysaccharide vaccine and one dose of inactivated hepatitis A vaccine on days 0 and 28, respectively. Adverse events were collected for 28 days after each dose. Blood samples were taken on days 0, 4, 14, 28, 32, 42, and 56 after the first dose to evaluate neutralizing antibody titers and laboratory parameters of coagulation function and blood glucose. Results: Fourteen days after the second dose of CoronaVac, the seroconversion rates of neutralizing antibodies against the prototype strain and beta, gamma, and delta variants of concern (VOC) of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) reached peak values of 89.31%, 23.3%, 45.3%, and 53.5%, respectively. The incidence of adverse reactions was 43.6% and 52.2% in the CoronaVac group and in the control group, respectively. All were mild or moderate in severity. For the laboratory parameters, there was no difference in the means of any parameter between the two groups at any time point, except for the D-dimer on day 14. However, the D-dimer in the CoronaVac group decreased on day 14 compared to the value at baseline, while a higher D-dimer value, instead of a decreased D-dimer value, was a risk factor for TTS. Conclusions: CoronaVac showed a good safety profile and could induce a humoral response against the prototype and VOCs of SARS-CoV-2 in adults 18 years or older, with no abnormal effects on laboratory parameters of blood glucose and coagulation function.